Exploring Green Chemistry: A Practicum Handbook for 11th Grade Science Students - Mutiara Maharani; Elvy Mawarnis; Akrajas Ali Umar (International Journal of Contextual Science Education, 2024)
The development of this practicum handbook aims to determine the validity of green chemistry-based chemistry practicum handbooks and to determine the practicality of green chemistry-based chemistry practicum handbooks. Research with the title "Development of a Green Chemistry-Based Chemistry Practicum handbook for 11th Grade Science Students." With the Research and Development (R&D) approach, the researcher has finished. The research was conducted at State Senior High School (SMAN) 2 Sungai Tarab, This research was conducted using the 4D model, namely (define, design, development, and disseminate), but researchers only carried out up to the development stage. At the feasibility stage, the green chemistry-based chemistry practicum handbook based on the validation results obtained 87.46%, with a very valid category. 2. At the practicality stage based on the student response questionnaire, the results were 85.41%, with a very practical category.